The relationship between learning organization climate and e-learning system success; moderating role of e-learning system quality - Peltek, Pelin (My University, 2008)
Endüstri devrimi sonunda, hızla değişen dünyaya bağlı olarak kuruluşlar birçok terimle yüzleşmek zorunda kalmışlardır. Bu durum hem şirketlerin hem de çalışanların devamlı gelişmesini ve öğrenmesini zorunlu hale getirdi. Örgütler ve kuruluşlar bu hızlı değişim sürecinde ayakta kalabilmek, rekabet edebilmek ve kendi sektörlerinde güçlü olabilmek için birçok metod geliştirip uygulamaya başladılar. Bu metodlardan bir tanesi de şirkette devamlı öğrenmeyi teşvik etmek ve öğrenmeyi sağlayacak sistemler kurmak oldu. Devamlı öğrenmeye önem veren şirketler “öğrenen örgütler” olarak literatürde yerini aldı. Teknolojinin ilerlemesiyle e-öğrenme şirketlerde çalışanların öğrenmesini destekleyici unsur olarak yer almaya başladı. Bu çalışma algılanan öğrenen örgüt iklimi ve e-öğrenme sistemi başarısı arasındaki ilişkiyi araştırmak için yapılmıştır. Buna ek olarak, e-öğrenme sistemi kalitesinin algılanan öğrenen örgüt iklimi ile e-öğrenme sistemi başarısı arasındaki ilişkiye moderatör etkisi araştırılmıştır. Analizlerin temel sonuçları şunlardır: 1. Algılanan öğrenen örgüt iklimi ile e-öğrenme sistemi başarısı arasında pozitif yönde anlamlı ilişki vardır. 2. E-öğrenme sistemi kalitesinin, algılanan öğrenen örgüt iklimi ile e-öğrenme sistemi başarısı arasındaki ilişkiye moderatör etkisi bulunamamıştır.

As a result of industrial revolution, organizations have to face many terms due to the accelerating change in the world. This case forced either organizations or employees improve and learn continuously themselves. During this rapid process organizations and corporations are developing and applying numerous methods to compete and stay alive and to be stronger in their sector. One of these methods is to encourage continuous learning and establish systems which provide this. The companies that give importance to continuous learning are called as “Learning Organizations” in the literature. As a consequence of technical improvements, e-learning takes place as supportive factor for learning of employees in corporations. This study was made in order to investigate the relationship between perceived learning organization climate and e-learning system success. In addition to this, the moderator effect of e-learning system quality on the relationship between perceived learning organization climate and e-learning system success was examined. The analysis yielded the following main results: 1. There is a positive and significant correlation between perceived learning organization climate and e-learning system success (ELSS). 2. E-learning system quality (ELSQ) has no significant moderating effect on the relationship between perceived learning organization climate and e-learning system success (ELSS). learning, electronic learning, learning organizations
Keywords: E-Öğrenme; Elektronik Öğrenme; Örgüt İklimi; Uzaktan Eğitim